Lifestyle modifications and non-pharmacological management in elderly hypertension - Tsai, Hao-Yuan; Chuang, Hung-Jui; Liao, Wei-Hsiang; Wang, Yi-Jie; Li, Pei-Hsuan; Wang, Wen-Ting; Liao, Shih-Cheng; Yeh, Chih-Fan; Chen, Pey-Rong; Lai, Tai-Shuan; Lin, Hung-Ju; Cheng, Shao-Yi; et al. (Journal of the Formosan Medical Association, 2025)
Many studies have examined the effectiveness of lifestyle modifications such as exercise, diet, weight loss, and stress reduction in controlling hypertension in elderly individuals, and several meta-analyses have reported that both aerobic and resistance exercise can reduce blood pressure in this population. In addition, the higher sensitivity to sodium in elderly individuals highlights the importance of restricting salt intake for blood pressure control. Low-sodium salt or potassium supplementation can help with blood pressure control in elderly individuals with hypertension. Several clinical trials have shown that both the Dietary Approaches to Stop Hypertension (DASH) and a Mediterranean diet pattern are effective in reducing blood pressure in older hypertensive patients. Although moderate alcohol consumption does not appear to negatively impact blood pressure control in older adults, blood pressure increases along with heavy alcohol intake. Some studies have indicated that coffee intake increases blood pressure in elderly hypertensive subjects, especially for those who consume more than 3 cups a day. Clinical studies have shown that weight loss through exercise and diet control is beneficial for controlling hypertension in elderly individuals. Anxiety, depression and insomnia also appear to have an impact on elderly hypertension. In this review, we discuss the effectiveness of lifestyle modifications and non-pharmacological management of these factors and their impact on hypertension in elderly individuals, and how to effectively implement them in real-world settings.